Mednarodna prepoznavnost Oddelka za geografijo Filozofske fakultete Univerze v Mariboru - Lorber, Lučka (Revija za geografijo, 2013)
The Department of Geography is internationally recognized in the closer regional, European and global spaces. When it comes to development of the field of geography, the department affiliates with geography departments of other universities and dedicates a lot of attention to researching border-area and cross-border spatial problems. It plays an important role in the area of science and research work when it comes to understanding spatial reality in the broader context of researching social, cultural and political aspects that are typical of individual periods during the last fifty years. International student-professor cooperation has especially progressed after the entry of Slovenia into the European Union. Teachers participate at international scientific congresses, give visiting lectures and attend summer schools. The department's international activity reflects in a growing number of published scientific articles in renowned international magazines and scientific papers in scientific monographs. Participation in scientific and research projects strengthens international recognisability of the Department of Geography of the Faculty of arts of the University of Maribor.
Keywords: European research programs; evropski raziskovalni programi; exellence; Faculty of Arts; Filozofska fakulteta; Filozofska fakulteta, Oddelek za geografijo; international cooperation; mednarodno sodelovanje; mobility; mobilnost; odličnost; prepoznavnost; recognition; study programs; študijski programi